2022
DOI: 10.3390/min12030342
|View full text |Cite
|
Sign up to set email alerts
|

Design and Computational Analyses of Nature Inspired Unmanned Amphibious Vehicle for Deep Sea Mining

Abstract: This paper presents the design calculations, implementations, and multi-engineering based computational constructions of an unmanned amphibious vehicle (UAmV) which efficiently travels underwater to detect and collect deep-sea minerals for investigations, as well as creative usage purposes. The UAmV is expected to operate at a 300 m depth from the water surface. The UAmV is deployed above the water surface near to the approximate target location and swims underwater, checking the presence of various mining, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Here the wing designs from the tropic bird which is the double tabard wing and the location of the wing is high wing. A large size fixed wing is designed for high lift generation, so that the lift and buoyancy force overcomes the gravity force to make the UAV float [47,48]. The wingspan of the UAV is taken from an adult tropic bird wing.…”
Section: Design Of Uav's Wing At Aerodynamic Environmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here the wing designs from the tropic bird which is the double tabard wing and the location of the wing is high wing. A large size fixed wing is designed for high lift generation, so that the lift and buoyancy force overcomes the gravity force to make the UAV float [47,48]. The wingspan of the UAV is taken from an adult tropic bird wing.…”
Section: Design Of Uav's Wing At Aerodynamic Environmentsmentioning
confidence: 99%
“…The relationship between wingspan, chord length, and wing area for a constant-chord swept-forward wing is given in Equation ( 5) [13,16,23,47,[53][54][55][56][57].…”
Section: Design Of Constant-chord Swept-forward (Ccsf) Wingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioinspired design is a field that has yielded successful products/processes [ 26 ] within several disciplines during the last decade, including: electric power generation [ 27 , 28 ], architectural design [ 29 , 30 ], materials science [ 31 ], medicine [ 32 , 33 ], and marine robotic systems [ 34 , 35 , 36 , 37 , 38 , 39 ], among others. Within the field of underwater vehicles, several research works have been reported during the last two decades.…”
Section: Introductionmentioning
confidence: 99%